S74 Is bronchoscopy needed in children with persistent bacterial bronchitis?. (14th November 2013) - Narang, RK; Bakewell, K; Peach, J; Clayton, S; Samuels, M; Alexander, J; Lenney, W; Gilchrist, FJ
Abstract : Introduction and Objectives: Persistent bacterial bronchitis (PBB) is increasingly recognised as a cause of chronic cough in young children but there is lack of consensus about investigation and treatment. At UHNS, children with a wet cough for >6 weeks unresponsive to oral antibiotics prescribed by the GP are investigated with CXR, baseline immune function and flexible bronchoscopy with bronchoalveolar lavage (FB-BAL). Patients with confirmed PBB are then treated with a prolonged course of an appropriate antibiotic. Some centres reserve FB-BAL for those who do not respond to blind treatment with co-amoxiclav or clinically relapse. The objective was to review bronchoscopic findings and immune function in children with chronic cough to determine which investigations are necessary. Methods: A retrospective case note review of all children investigated for chronic cough between May 2011 and June 2013. Results: The notes of 44 children with chronic cough were reviewed. BAL samples were taken from 6 lobes in every patient. Median (IQR) age at bronchoscopy was 3.3 (1.8–4.4) years. Positive BAL cultures were obtained from 35 patients (80%). Ten patients (23%) isolated ≥2 organisms. Haemophilus influenza was identified in 20 (46%), Moraxella catarrhalis in 11 (25%), Staphylococcusl aureus in 10 (23%) and Streptococcus pneumoniae in 6 (14%). Candida albicans, Group A Streptococcus, Haemophilus parainfluenzae and a gram negative bacillus were each identified in 1 patient (2%). In 13 (30%) at least 1 organism was isolated that was unlikely to respond to co-amoxiclav. If the right middle lobe (RML) had been the only lobe sampled (as per ERS guidance) organisms would have been missed in 14 patients (32%). Suboptimal functional antibodies to Haemophilus influenza or Pneumococcus were identified in 7 patients (16%). Appropriate antibiotics were prescribed for all patients with a positive culture. Co-amoxiclav was the most commonly prescribed antibiotic and was used in 20 patients (57%). Treatment duration varied between 4 and 8 weeks. Conclusions: FB-BAL is a useful investigation to aid the diagnosis and guide treatment in PBB. The best time to perform FB-BAL is not known. In PBB a number of organisms will be missed if BAL is only taken from the RML.